Penguatan Personal Selling Bagi Pemilik dan Pegawai Warung Tegal Kharisma di Tebet Barat, Tebet, Jakarta Selatan - Aska Leonardi; Sumiyati Sumiyati; Arry Rahayunianto (BERDAYA: Jurnal Pendidikan dan Pengabdian Kepada Masyarakat, 2022)
Providing knowledge and understanding about personal selling or face-to-face selling to the owners and employees of Warung Tegal Kharisma in Tebet Barat Village, Tebet District, South Jakarta. Since the Covid-19 pandemic occurred, culinary entrepreneurs can no longer optimally sell their wares directly to consumers due to the policy of Enforcement of Community Activity Restrictions (PPKM). However, in mid-2022, the government has allowed the restaurant business to reopen, so the entrepreneur Warung Tegal (Warteg) Kharisma also takes advantage of this opportunity to return to selling culinary delights after being closed for two years during the pandemic. In order for Warteg Kharisma entrepreneurs to return to profit, and be able to cover losses during the pandemic, then there is a strengthening of face-to-face marketing communications as an effort aimed at increasing the personal selling ability of Warteg Kharisma owners and employees, so that business continuity occurs through increasing the number of sales, and business profits.